Bazı aile hekimliği pilot uygulama birimlerinde birinci basamak değerlendirme ölçeği (BDÖ) (Primary Care Assessment Survey) ile sağlık hizmet özelliklerinin değerlendirilmesi - Tülay Lağarlı; Erhan Eser; Mustafa Akdeniz; Bahar Aydoğdu; Ümit Baklaya; Canan Fıra; Adnan Saatçioğlu; Burak Sönmez; Eylül Taner; Seval Tığlı; Koray Topçu; Başak Yıldız; et al. (Turkish Journal of Public Health, 2011)
Bu kesitsel çalışmanın amacı 2008 yılından başlayan Aile  Özet Amaç: 1 Ocak 2008’de başlayan Aile Hekimliği Manisa İli pilot uygulamasının yapısal ve işleyiş özelliklerini PCAS (Primary Care Assessment Survey) Birinci Basamak Değerlendirme Ölçeği ile değerlendirmektir. Yöntem: Çalışma 20.8.2009 - 27.8.2009 tarihleri arasında Manisa merkez ilçede 6 aile sağlığı birimine bağlı bölgede yürütülmüştür. Araştırma bölgesindeki toplam hane sayısı 6900 dür. Küme örnekleme yöntemi ile 360 haneden birer kişiye ulaşılarak, 18 yaş üstü 381 bireye PCAS anketi yüz yüze görüşme yöntemiyle uygulanmıştır. Araştırmaya katılım oranı (327/360) %90’dır. Bulgular: Örneğin yaş ortalaması 41.2±13.9 dur. Araştırma kapsamındaki kişilerin %86.4’ü kadındır. Araştırma grubunun %16.5’i eğitimsiz, %17.0’ı ise sağlık güvencesi olmayanlar ve yeşil kart sahipleridir. Ölçek puanları, boyutlara göre: Ulaşılabilirlik:53.56±17.41; Süreklilik: 74.01±11.95; Kapsayıcılık: 49.04±20.51; Eşgüdüm: 43.13±43.3; Hizmet memnuniyeti :70.01±13.57; Hekimin kişisel yakınlığı :71.94±17.41 ve Güven :71.95±11.96 ‘dır. En başarılı özellik sürekliliktir. Ulaşılabilirlik: Hanede 5 yaş çocuk ve 0-12 aylık bebek varlığında, sağlık güvencesi ve yeşil kart sahibi olanlarda, hanede kronik hastalığı olan birey varlığında ve ailenin tüm bireyleri aynı aile hekimine kayıt olanlarda daha yüksektir. Süreklilik: Yaşlı ve kadınlarda ve eğitimsizlerde, beş yaş altı çocuk ve kronik hasta bulunmayan hanelerde daha yüksek bulunmuştur. Kapsayıcılık: Yaş ilerledikçe ve sağlık güvencesi olanlarda, hanede kronik hastalıklı ve engelli birey varlığında daha yüksektir. Çok değişkenli analizler sonucunda sağlık güvencesi, yaş, eğitim, aynı aile hekimine kayıtlı olma etkili bulunmuştur. Yapısal özet boyut, ilişki özet boyutuna göre daha düşük puan almıştır. Sonuç: Manisa Merkez İlçede Aile Hekimliği uygulamasında, kadın ve beş yaş altı çocuk risk gruplarına öncelikli yaklaşımın sürdüğü, yaşlılık sağlık sorunları ile ilgili yeni bir yaklaşımın oluşmakta olduğu görülmüştür. Anahtar kelimeler: Birinci basamak sağlık hizmeti özellikleri, aile hekimliği, PCAS Abstract Aim: The objective of this cross-sectional study is to assess the structural and functional properties of the recently (in 2008) promoted Family Physician Services by using the PCAS (Primary Care Assessment Survey: Primary Care Evaluation Scale) scale.Methods: The study was conducted between 20.08.2009 and 27.8.2009 in 6 Family Physician Units (FPUs) of Manisa city. The household universe was 6900 and 381 persons living in 360 Households (sample size) were interviewed by a face to face approach. Results: The mean age of the study sample was 41.2 ± 13.9 (min-max 18-77) and 86.4% of the sample was female. 16.5% of respondents were illiterate; 17.0% were green card holders; 85.6% were married and 72.7% were living in core families. 98.4% of the households had safe and clean tap water and 89.8% of the households had an inside toilet, the rest had outdoor toilets. The dimensional scores of the PCAS were as follows: Accessibility 53.56 ± 17.41; Continuity 74.01 ± 11; Comprehensiveness 49.04 ± 20.51; Coordination 43.13 ± 43.3; Service satisfaction 70.01 ± 13.57; Trust 71.94 ± 17.41 and Interpersonal treatment 71.95 ± 11, 96. Among the four structural dimensions of the PCAS, the highest score was obtained for the Continuity dimension whereas the Accessibility, Comprehensiveness and Coordination dimension scores were rather low. The results of the univariate analyses indicated that the Accessibility score was significantly higher when: neonate or children under five were in the household; health insurance and/or green card was available; a person with a chronic disease was present in the household, and when all of the household members were registered with the same family physician. The Continuity score was significantly higher for persons who were older, female, or had a low educational level and in those households with any children under five or presence of any person with a chronic disease in the household. The Comprehensiveness score was also significantly higher for older persons, those who had health insurance, those with a person with a chronic disease or a disabled person in the household. The Service satisfaction dimension was better for those with a low educational level and those aged over 65. The Personal relationships dimension score was only affected by an older age and the Trust score was found higher in older persons and those who are chronically ill or disabled. Service satisfaction, personal relationships and trust scores were higher if all of the household members were registered with the same family physician. As for the results of multivariate analysis, being covered by health insurance, age, level of education, and having the family registered with the same family physician, were the variables that affected the dimension scores mentioned above. Conclusion: In general, structural (four) dimension scores were found to be low whereas patient-physician relationship (three) domain scores were found in a normal range. In addition to these findings, the elements of the recently modified PHC system were found to be poor in general except for the continuity element. Key words: Primary health care assessment, family physician services, PCAS